The Modality Effect on Delayed Free Recall in Non-demented Patients With Mild Parkinson’s Disease Progression - Kormas, Constantinos; Zalonis, Ioannis; Evdokimidis, Ioannis; Kapaki, Elisabeth; Potagas, Constantin (Frontiers in Aging Neuroscience, 2019)
Background: The modality effect plays the central role in learning and memory functions. Retrieval failure constitutes a common memory impairment that occurs among patients with Parkinson’s disease (PD). However, little knowledge exists about the relation between modality effect and delayed recall impairment in PD. The primary goal of this study was to compare delayed free recall performance between three different memory modalities (verbal, visual, and cross visual-verbal) in a sample of non-demented patients with mild PD progression. The secondary goal was to explore the frequency of deficient performance on the basis of normative comparisons on each of the three delayed free-recall measures. Method: A total of 71 non-demented patients with mild Parkinson’s disease progression were recruited for the administration of the Montreal Cognitive Assessment (MoCA), the Rey Auditory Verbal Learning Test (RAVLT), the Rey Osterrieth Complex Figure Test (ROCFT), and the Greek Version of Face-Name Associative Memory Examination (GR-FNAME12). Results: The percentages of deficient-performances for the three delayed free recall measures were 45.1% (32/71), 39.4% (28/71) and 31% (22/71) for the GR-FNAME12, ROFCT and RAVLT, respectively. The results indicated no significant difference between performances of the GR-FNAME12 and ROCFT, both of which were significantly lower than performance on the RAVLT. Conclusions: In conclusion, delayed free recall appears to be more severely affected in the cross visual-verbal and visual memory modalities than in verbal-memory modalities in the early phase of PD progression.